Are midwives in the Netherlands satisfied with their jobs? A systematic examination of satisfaction levels among hospital and primary-care midwives in the Netherlands - Doug Cronie; Hilde Perdok; Corine Verhoeven; Suze Jans; Marieke Hermus; Raymond de Vries; Marlies Rijnders (BMC, 2019)
Abstract Background Job satisfaction is generally considered to be an important element of work quality and workplace relations. Little is known about levels of job satisfaction among hospital and primary-care midwives in the Netherlands. Proposed changes to the maternity care system in the Netherlands should consider how the working conditions of midwives affect their job satisfaction. Aim We aimed to measure and compare job satisfaction among hospital and primary-care midwives in the Netherlands. Methods Online survey of all practising midwives in the Netherlands using a validated measure of job satisfaction (the Leiden Quality of Work Questionnaire) to analyze the attitudes of hospital and primary-care midwives about their work. Descriptive and inferential statistics were used to assess differences between the two groups. Results Approximately one in six of all practising midwives in the Netherlands responded to our survey (hospital midwives n = 103, primary-care midwives n = 405). All midwives in our survey were satisfied with their work (n = 508). However, significant differences emerged between hospital and primary-care midwives in terms of what was most important to them in relation to their job satisfaction. For hospital midwives, the most significant domains were: working hours per week, workplace agreements, and total years of experience. For primary-care midwives, social support at work, work demands, job autonomy, and the influence of work on their private life were most significant. Conclusion Although midwives were generally satisfied, differences emerged in the key predictors of job satisfaction between hospital and primary-care midwives. These differences could be of importance when planning workforce needs and should be taken into consideration by policymakers in the Netherlands and elsewhere when planning new models of care.